The Role of Human Capital to the Improvement of Employee Performance in Fisheries Companies in North Sulawesi Province - Wehelmina Rumawas (AIBPM Publisher, 2018)
The aim of study is to analyze and explain the influence of human capital on employee performance. In this study using human capital as an independent variable and employee performance as the dependent variable. This study uses a survey method with a quantitative descriptive approach, the location of the research on Fisheries Companies in North Sulawesi Province.The sample in this study amounted to 152 respondents. To determine the sample, to be used area proportional random sampling technique. The data that has been netted with a questionnaire is then rated and tabulated for further analysis using multiple regression. The results of the study show that human capital through education level, work experience and competency variables have a positive and significant effect on employee performance.